DISEASE DETECTION BY USING IMAGE PROCESSING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The analysis of malaria is based on novel Annular Ring Ratio Method which is already implemented, tested and validated in MATLAB. The method detects the blood components such as the Red Blood Cells RBCs White Blood Cells WBCs and identifies the parasites in the infected RBCs. Dengue fever is a viral disease and it is a major issue in many developing countries, including India. The main objective is to detect and count platelet to diagnose Dengue Haemorrhagic Fever this reduces labor intensive, time and cost. There is a solution in hands of digital image processing to face this challenge. Segmentation techniques and morphological operation are applied to investigate the number of platelets which is used to diagnose dengue using the microscopic image of blood smear. The platelet count is estimated using various Segmentation techniques and morphological operations and with the help of the platelets count dengue fever infection is detected. One of the morphological operations called flood fill is utilized to detect platelet with platelet size. In many primary health care centers blood cell counting is typically performed manually, which is very difficult and requires expert lab technician. This procedure needs a digital camera attached with traditional magnifying microscope where the advanced camera is associated with PC. The expense of the proposed hardware is cost efficient.